2021
DOI: 10.7554/elife.62800
|View full text |Cite
|
Sign up to set email alerts
|

Mapping immune variation and var gene switching in naive hosts infected with Plasmodium falciparum

Abstract: Falciparum malaria is clinically heterogeneous and the relative contribution of parasite and host in shaping disease severity remains unclear. We explored the interaction between inflammation and parasite variant surface antigen (VSA) expression, asking whether this relationship underpins the variation observed in controlled human malaria infection (CHMI). We uncovered marked heterogeneity in the host response to blood challenge; some volunteers remained quiescent, others triggered interferon-stimulated inflam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
36
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 106 publications
6
36
1
Order By: Relevance
“…Considering that individual parasites express a single var gene, this result indicates that the parental population was relatively homogeneous, such that the vast majority of individual parasites expressed the same var gene ( var2csa ), whereas after passage through transmission stages the population became heterogeneous, with different individual parasites expressing different var genes. Some of the most highly expressed var genes in vNF54 lines coincided with the most highly expressed genes in a recent CHMI study using the 3D7 line to infect volunteers ( 52 ) ( Fig. S3A ), and preferential upregulation of type B var genes in parasites from the volunteers is also consistent with previous reports from other CHMI studies ( 36 , 48 , 52 ).…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Considering that individual parasites express a single var gene, this result indicates that the parental population was relatively homogeneous, such that the vast majority of individual parasites expressed the same var gene ( var2csa ), whereas after passage through transmission stages the population became heterogeneous, with different individual parasites expressing different var genes. Some of the most highly expressed var genes in vNF54 lines coincided with the most highly expressed genes in a recent CHMI study using the 3D7 line to infect volunteers ( 52 ) ( Fig. S3A ), and preferential upregulation of type B var genes in parasites from the volunteers is also consistent with previous reports from other CHMI studies ( 36 , 48 , 52 ).…”
Section: Resultssupporting
confidence: 89%
“…Some of the most highly expressed var genes in vNF54 lines coincided with the most highly expressed genes in a recent CHMI study using the 3D7 line to infect volunteers ( 52 ) ( Fig. S3A ), and preferential upregulation of type B var genes in parasites from the volunteers is also consistent with previous reports from other CHMI studies ( 36 , 48 , 52 ).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The algorithm was developed here specifically to determine whether any metabolites could be identified that changed in abundance in similar ways across a series of distinct fever-associated diseases. These include Zika virus infection in patients from Ecuador [13], Leishmaniasis patients from Spain [14] and uncomplicated malaria infected volunteers from the UK [15]. The samples had all been run previously using the same LC-MS platform (Glasgow Polyomics, University of Glasgow, UK).…”
Section: Introductionmentioning
confidence: 99%